A STUDY ON PRESCRIBING PATTERN OF ANTIMICROBIAL AGENTS IN THE NEONATAL INTENSIVE CARE UNIT OF A TERTIARY CARE TEACHING HOSPITAL IN PUDUCHERRY, SOUTH INDIA - J, Pandiamunian; Salwe, Kartik J; G, Somasundaram; Kolasani, Bhanu Prakash (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: This study was done to evaluate the current prescribing and usage pattern of antimicrobial agents (AMAs) in the neonatal intensive care unit (NICU). Methods: A prospective, hospital-based, cross-sectional study (prescription audit) was carried out between May and August 2012 in the NICU of a Teaching Hospital. Data were collected by reviewing case records of all neonates admitted to the NICU during the study period. Results: A total of 120 case records were reviewed and 100 were eligible to be included in the study. Out of the 100, no antimicrobial prescription was made in 35 case records. Remaining 65 (65%) were prescribed at least one AMA. 167 AMA prescriptions were made in total and average number of AMAs utilized per neonate was 1.670. Cefotaxime (24.6%) was the most commonly prescribed AMA followed by amoxicillin (23.4%). Aminoglycosides (43.7%) were the commonly prescribed group of AMAs followed by penicillins (28.7) and cephalosporins (24.6%). Most of the AMAs were prescribed to non-bacteriologically proven infections (50.5%). Among the 167 AMA prescriptions, 104 (62.28%) were made in their brand names and 63(37.72%) were made in their generic names. Discussion and Conclusion: This study highlights current usage of AMAs in the NICU of a tertiary care teaching hospital in Puducherry. AMAs were found to be prescribed frequently without bacteriological evidence and in their brand names. This necessitates the need for motivating doctors to improve AMA prescriptions with supportive bacteriological evidence and in generic names. Keywords: Antimicrobial agents, Neonatal intensive care unit, Generic drugs, Non-bacteriologically proven infections.